(untitled) (Altre Modernità, 2016)
Whereas technical manipulation in the form of necessary “textual dislocations” (Diaz-Cintas 2012: 284) may be seen as a common object of study in audiovisual translation (AVT), ideological manipulation or a deliberate change from what is said (or shown) in the original (ibid) still seems to be under developed in the discipline. However, power plays have a lot to say in AVT, as can be illustrated with the repressive forces of censorship at certain times and periods. In the case of Franco’s dictatorship in Spain (1939-1975 and beyond) the control of every cultural product which entered the country, both in written or audiovisual form, functioned as an ideological gatekeeper. The last years, however, were marked by a progressive weakening both of the regime and of its censoring mechanism. By then, the massive importation of North American best- selling novels took place, novels which were either commonly filmed afterwards or turned into a TV series, making them famous worldwide. This nurturing from literature of the film industry in the form of tie-ins was a very common synergy at the time, denounced and considered by some as commercial manipulation and social alienation (Carrero Eras 1977). In the present article, the effects of the censoring mechanism on some North American best-selling novels and their film counterparts will be examined, trying to reveal the manoeuvrings at stake and thus contribute to increase the research on the matter and, at the same time see if, the solitary act of reading versus the public broadcasting of a film had a say in the harshness applied to a product derived from the same root.